Arranging the Self: Literary and Archival Perspectives on Writers’ Archives - Douglas, Jennifer; MacNeil, Heather (Archivaria, 2009)
This article reports on a small exploratory research project undertaken by the authors on the archives of three well-known Canadian writers − L.M. Montgomery, Marian Engel, and Alice Munro – for the purpose of assessing whether and to what extent we can know writers – their character and intentions – through their archives. The three writers’ archives were examined through two interpretive frameworks: the archival principles of arrangement and the literature on life writing. The authors found that the capacity of a writer’s archive to reveal character and intention, inevitably, is constrained by the writer’s own efforts to conceal and edit the self, and by the imposition of intentions of persons other than the writer on the archive. RÉSUMÉ Ce texte rend compte d’un petit projet de recherche exploratoire que les auteures ont mené en examinant les fonds d’archives de trois écrivaines canadiennes bien connues – L. M. Montgomery, Marian Engel et Alice Munro – afin de déterminer s’il est possible de connaître les écrivaines, leurs personnalités et leurs intentions, à partir de leurs archives, et si oui, dans quelle mesure. Les auteures ont examiné les archives des trois écrivaines en se servant de deux cadres d’interprétation : les principes archivistiques du classement et les textes théoriques portant sur le récit de vie. Les auteures ont conclu que la possibilité qu’un fonds d’archives d’écrivain révèle la personnalité et l’intention de l’auteur est inévitablement contrainte à la fois par les efforts mêmes de l’écrivain pour cacher ou réviser sa vie et par l’intervention de d’autres personnes qui peuvent imposer leur propre intention sur le fonds d’archives.